Circulating plasma phospholipid fatty acids and risk of pancreatic cancer in a large European cohort. Issue 10 (21st September 2018) - Matejcic, M.; Lesueur, F.; Biessy, C.; Renault, A.L.; Mebirouk, N.; Yammine, S.; Keski‐Rahkonen, P.; Li, K.; Hémon, B.; Weiderpass, E.; Rebours, V.; Boutron‐Ruault, M.C.; et al.
Abstract : There are both limited and conflicting data on the role of dietary fat and specific fatty acids in the development of pancreatic cancer. In this study, we investigated the association between plasma phospholipid fatty acids and pancreatic cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. The fatty acid composition was measured by gas chromatography in plasma samples collected at recruitment from375 incident pancreatic cancer cases and375 matched controls. Associations of specific fatty acids with pancreatic cancer risk were evaluated using multivariable conditional logistic regression models with adjustment for established pancreatic cancer risk factors. Statistically significant inverse associations were found between pancreatic cancer incidence and levels of heptadecanoic acid (ORT3‐T1 [odds ratio for highest versus lowest tertile] =0.63; 95%CI[confidence interval] = 0.41–0.98; p trend = 0.036), n‐3 polyunsaturated α‐linolenic acid (ORT3‐T1 = 0.60; 95%CI = 0.39–0.92; p trend = 0.02) and docosapentaenoic acid (ORT3‐T1 = 0.52; 95%CI = 0.32–0.85; p trend = 0.008). Industrial trans‐fatty acids were positively associated with pancreatic cancer risk among men (ORT3‐T1 = 3.00; 95%CI = 1.13–7.99; p trend = 0.029), while conjugated linoleic acids were inversely related to pancreatic cancer among women only (ORT3‐T1 = 0.37; 95%CI = 0.17–0.81; p trend = 0.008). Among current smokers, the long‐chain n‐6/n‐3 polyunsaturated fatty acids ratio was positively associated with pancreatic cancer risk (ORT3‐T1 = 3.40; 95%CI = 1.39–8.34; p trend = 0.007). Results were robust to a range of sensitivity analyses. Our findings suggest that higher circulating levels of saturated fatty acids with an odd number of carbon atoms and n‐3 polyunsaturated fatty acids may be related to lower risk of pancreatic cancer. The influence of some fatty acids on the development of pancreatic cancer may be sex‐specific and modulated by smoking. Abstract : What's new? This is the first study exploring the association between fatty acid biomarkers and pancreatic cancer (PC) risk in an epidemiological setting. The findings support previous evidence on the association between dairy products and seed and marine food and the risk of PC. Furthermore, industrial trans fatty acids were positively associated with PC risk among men, while conjugated linoleic acids conferred a significantly reduced risk among women. The long‐chain n‐6/n‐3 PUFA ratio conferred a higher risk of PC among smokers. Using circulating biomarkers may thus be important for identifying the potential fatty acid isomers and their biological effects leading to PC.